Aging and Comorbidities in Acute Pancreatitis II.: A Cohort-Analysis of 1203 Prospectively Collected Cases - Szakács, Zsolt; Gede, Noémi; Pécsi, Dániel; Izbéki, Ferenc; Papp, Mária; Kovács, György; Fehér, Eszter; Dobszai, Dalma; Kui, Balázs; Márta, Katalin; Kónya, Klára; Szabó, Imre; et al. (Frontiers in Physiology, 2019)
Introduction: Our meta-analysis indicated that aging influences the outcomes of acute pancreatitis (AP), however, a potential role for comorbidities was implicated, as well. Here, we aimed to determine how age and comorbidities modify the outcomes in AP in a cohort-analysis of Hungarian AP cases. Materials and Methods: Data of patients diagnosed with AP by the revised Atlanta criteria were extracted from the Hungarian Registry for Pancreatic Patients. Outcomes of interest were mortality, severity, length of hospitalization, local, and systemic complications of AP. Comorbidities were measured by means of Charlson Comorbidity Index (CCI) covering pre-existing chronic conditions. Non-parametric univariate and multivariate statistics were used in statistical analysis. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Results: A total of 1203 patients from 18 centers were included. Median age at admission was 58 years (range: 18–95 years), median CCI was 2 (range: 0–10). Only severe comorbidities (CCI ≥ 3) predicted mortality (OR = 4.48; CI: 1.57–12.80). Although severe comorbidities predicted AP severity (OR = 2.10, CI: 1.08–4.09), middle (35–64 years) and old age (≥65 years) were strong predictors with borderline significance, as well (OR = 7.40, CI: 0.99–55.31 and OR = 6.92, CI: 0.91–52.70, respectively). Similarly, middle and old age predicted a length of hospitalization ≥9 days. Interestingly, the middle-aged patients (35–64 years) were three times more likely to develop pancreatic necrosis than young adults (OR = 3.21, CI: 1.26–8.19), whereas the old-aged (≥65 years) were almost nine times more likely to develop systemic complications than young adults (OR = 8.93, CI: 1.20–66.80), though having severe comorbidities (CCI ≥ 3) was a predisposing factor, as well. Conclusion: Our results proved that both aging and comorbidities modify the outcomes of AP. Comorbidities determine mortality whereas both comorbidities and aging predict severity of AP. Regarding complications, middle-aged patients are the most likely to develop local complications; in contrast, those having severe comorbidities are prone to develop systemic complications. Studies validating the implementation of CCI-based predictive scores are awaited.